EFEKTIVITAS PENGGUNAAN DANA DESA PADA PROGRAM PEMBERDAYAAN MASYARAKAT DI DESA KANAWONG KECAMATAN SIAU BARAT KABUPATEN KEPULAUAN SIAU TAGULANDANG BIARO TAHUN ANGGARAN 2017 - SANDALA, FASCAL MAREL; RORONG, ARIE JUNUS; LONDA, VERY (Sam Ratulangi University, 2018)
This research aim to find out the effectiveness of the use of the village Fund programcommunity empowerment didesa Kanawong on fiscal year 2017. Research methods used in thisresearch is qualitative. The data used are composed of primary data and secondary data. Withthe technique of collecting data through observation, interview and documentation, dataobtained from various sources and analyzed with data reduction steps, the presentation of thedata and the withdrawal of the conclusion. Results of the study showed that the use of the fundsin the village of Kanawong sub-district of the Western Islands Regency Siau SITARO programeffectiveness to achieve the empowerment of communities in the measure of the transparency ofboth the program less efektiv village Government does not explain about the use of the villageFund, on aspects of participation is already running on the community through involvement inactivities of the integrated service post, while on the Government less look real on the trainingprogram the village chief and the posyandu activities, device already running and can beenjoyed by society, in contrast to training activities yet can be enjoyed. Posyandu program canbe completely accountable, but less on the training can be accounted for. Empowermentprogram on training does not continue the Government's work plan is seen from the village ofthe year 2018, posyandu empowerment as well as the budget continues to increase. Theconclusions and suggestions of transparency on the activities of the training of village chief anddevices as well as the activities of posyandu in village Kanawong less effective, participation isalready a real run on the society, training activities the village chief and the village has yet to bebe enjoyed while at posyandu activities can be enjoyed, the less training activities can beaccountable, the activities of posyandu can be accountable. Training activities do not continue,while the community empowerment Program for the empowerment of posyandu continues.Keywords : effectiveness, Village Fund, Empowerment